ANALISIS GAYA HIDUP PERILAKU KONSUMTIF MAHASISWA TERHADAP PENGARUH TEKNOLOGI INFORMASI DI KOTA BATAM - Riki (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2019)
This research was conducted in Batam City-Riau islands. The aim of the study was to find out how the lifestyle of consumptive behavior of students in Batam city today. This research is titled "Analysis of the lifestyle of consumptive behavior of students on the influence of information technology in the city of Batam". The focus of this research is, how and for the impact of the lifestyle of consumptive behavior of students, to the influence of information technology in the city of Batam. The author only took a student sample of 9 people. The study uses a qualitative descriptive approach. The data instruments used are observation, interviews, and documentation. The results showed that, in conducting research researchers found a consumptive lifestyle of students who are hyperriality, and hedonism to the influence of existing information technology. Students today tend to extravagance in consuming a product or item. With this, the lifestyle of consumptive behavior of students in the city of Batam become competitive, among fellow students who are one with the other. One example with the latest and more sophisticated smartphone output that provides full features but reasonably priced. The influence of information technology today, making students follow the fashion trend of today buy something that is not the main need (priority), but only the desire to follow the current trend.